PENGARUH KEPEMIMPINAN KEPALA SEKOLAH, IKLIM ORGANISASI DAN KOMPETENSI GURU TERHADAP KINERJA GURU SMP NEGERI 1 PALLANGGA KABUPATEN GOWA - Nelly Anita; Bahrun Amin; Muhammad Adil (UNIVERSITAS MUHAMMADIYAH MAKASSAR, 2021)
This research aims to determine whether there is an influence of Leadership, Organizational Climate, and Competence on the Performance of First Middle School Teachers (SMP) Negeri 1 Pallangga. This research is an ex-post facto research which is correlational in nature. The population of this research is SMP Negeri 1 Pallangga in Gowa Regency which consists of 75 people. This study uses a questionnaire instrument of Leadership, Organizational Climate, Teacher Competence, and Teacher performance. The statistical analysis used is descriptive analysis and inferential analysis. The results of the analysis show that the leadership of the principal at SMP Negeri 1 Pallangga is categorized as high, with an average score of 32,85 and a standard deviation of 7,86 and located in the 20 - 65 interval. Teacher competence is categorized as high, with an average score of 22,44 and a standard deviation of 4,29 and located at intervals of 10-30 and the work climate of teachers is categorized as high, with an average score of 21,75 and a standard deviation of 3,27 and located at intervals of 14 - 31 While teacher performance is categorized as high, with an average score of 23,45 and a standard deviation of 4,29 and is located at the interval 13-30 and categorized as high.Keywords: Principal Leadership, Organizational Climate, Teacher Competence and Teacher Performance